2017
DOI: 10.3399/bjgp17x691733
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ perceptions of their emerging general practice roles in UK primary care: a qualitative interview study

Abstract: BackgroundUK general practice is experiencing a workload crisis. Pharmacists are the third largest healthcare profession in the UK; however, their skills are a currently underutilised and potentially highly valuable resource for primary health care. This study forms part of the evaluation of an innovative training programme for pharmacists who are interested in extended roles in primary care, advocated by a UK collaborative ‘10-point GP workforce action plan’.AimTo explore pharmacists’ perceptions of primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
91
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 19 publications
7
91
0
Order By: Relevance
“…It may be that these courses need to be further and continually promoted. The networking opportunity of training events was valued, which was echoed in the Exeter training study . Independent Prescribing courses cover clinical and communication skills in detail.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be that these courses need to be further and continually promoted. The networking opportunity of training events was valued, which was echoed in the Exeter training study . Independent Prescribing courses cover clinical and communication skills in detail.…”
Section: Discussionmentioning
confidence: 99%
“…There is going to be an increased number going through courses to work in GP Practice; therefore, it is essential that courses have strong emphasis on the type of clinical and prescribing work that is being undertaken. The Exeter study noted the potential of a formal, standardised qualification in primary care pharmacy . A small qualitative study in London noted the importance of measuring impact of this new role in pharmacy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, over the past 12 months, directors from commissioning and delivery organisations within the NHS believe the quality of care in their area has deteriorated . Measures to meet the demand have included exploring new modes of service delivery, including increasing the availability of step‐down facilities, offering increased remuneration rates for agency staff and outsourcing elective care, as well as integrating services . With multiple contributory factors to the increases in demand, the service estimated deficits in the region of £873 million for 2016/17 .…”
Section: Introductionmentioning
confidence: 99%
“…Such errors included use of beta‐receptor antagonists in patients with asthma and angiotensin‐converting enzyme inhibitors in elderly patients without assessing electrolytes . Indeed, more recent work has demonstrated that pharmacists are enthusiastic to take on roles in non‐traditional care settings, such as general practices . Such studies highlight the positive impact pharmacists can have on patient outcomes and have provided an opportunity for pharmacists to contribute to the delivery of pharmaceutical care within emerging models of health service delivery.…”
Section: Introductionmentioning
confidence: 99%